Discontinuation of afterload-reducing drugs decreases left ventricular outflow tract obstruction in hypertrophic obstructive cardiomyopathy - Derda, Anselm A.; Abelmann, Malin; Sonnenschein, Kristina; Sieweke, Jan-Thorben; Bavendiek, Udo; Bauersachs, Johann; Thum, Thomas; Berliner, Dominik (Frontiers in Cardiovascular Medicine, 2024)
Hypertrophic cardiomyopathy (HCM), the most common genetic heart disease, is classified into hypertrophic non-obstructive and hypertrophic obstructive cardiomyopathy (HOCM). Patients with HOCM and coexisting heart failure or arterial hypertension are often prescribed afterload-reducing drugs. Although recommended in current guidelines, data on the direct effect of discontinuing afterload-reducing medication are scarce. This study aims to demonstrate the benefit of discontinuing afterload-reducing medication in HOCM patients.This monocentric retrospective analysis included 24 patients with HOCM with afterload-reducing medication, including angiotensin-converting enzyme inhibitors, angiotensin-1 receptor blocker and dihydropyridine-calcium channel blocker, at their first outpatient visit. Effects of discontinuing this medication on LVOTO were examined compared to patients with persistent use despite medical advice.16 patients discontinued their afterload-reducing drugs, resulting in a significant decrease in median LVOT gradient from 86.5 [60.5-109.3]mmHg to 61.5 [28.3-97.50]mmHg (p=0.0004). In 6 patients, beta-blocker therapy was initiated simultaneously, or the dose was increased. Regardless, LVOT gradient reduction was also significant in the remaining 10 patients (p=0.001). The gradient was not changed significantly in the 8 patients continuing their afterload-reducing medication.Discontinuation of afterload-reducing drugs significantly decreases LVOTO. Our study underscores the significance of abstaining from afterload-reducing drugs in HOCM patients, particularly in patients with concomitant hypertension or heart failure. According to recently published European guidelines, HOCM patients should preferably be treated with beta-blockers, non-dihydropyridinecalcium channel blockers.